In Silico-Based Design and In Vivo Evaluation of an Anthranilic Acid Derivative as a Multitarget Drug in a Diet-Induced Metabolic Syndrome Model - Héctor González-Álvarez; Astrid Bravo-Jiménez; Matilda Martínez-Arellanes; Gabriela Odette Gamboa-Osorio; Edwin Chávez-Gutiérrez; Lino A. González-Hernández; Karina Gallardo-Ignacio; Osvaldo J. Quintana-Romero; Armando Ariza-Castolo; Christian Guerra-Araiza; Laura Martino-Roaro; Dulce María Meneses-Ruiz; et al. (MDPI AG, 2021)
Metabolic syndrome (MetS) is a complex disease that affects almost a quarter of the world's adult population. In MetS, diabetes, obesity, hyperglycemia, high cholesterol, and high blood pressure are the most common disorders. Polypharmacy is the most used strategy for managing conditions related to MetS, but it has drawbacks such as low medication adherence. Multitarget ligands have been proposed as an interesting approach to developing drugs to treat complex diseases. However, suitable preclinical models that allow their evaluation in a context closer to a clinical situation of a complex disease are needed. From molecular docking studies, compound 1b, a 5-aminoanthranilic acid derivative substituted with 4'-trifluoromethylbenzylamino and 3',4'-dimethoxybenzamide moieties, was identified as a potential multitarget drug, as it showed high in silico affinity against targets related to MetS, including PPAR-α, PPAR-γ, and HMG-CoA reductase. It was evaluated in a diet-induced MetS rat model and simultaneously lowered blood pressure, glucose, total cholesterol, and triglyceride levels after a 14-day treatment. No toxicity events were observed during an acute lethal dose evaluation test at 1500 mg/kg. Hence, the diet-induced MetS model is suitable for evaluating treatments for MetS, and compound 1b is an attractive starting point for developing multitarget drugs.